Rodzina i rodzaj – biologiczne jednostki taksonomiczne w Słowniku języka polskiego pod redakcją Mieczysława Szymczaka - Chodera, Janina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The article opens with the presentation of the principles of formulation of Latin names of families and genera in the systematics of Carolus Linnaeus as well as the presentation of the presumptions adopted in the Polish terminology with reference to word-formation of the discussed taxonomical units (categories). Next, a detailed analysis has been presented of the structure of definitions referring to the designation family in the Dictionary of the Polish Language edited by Mieczysław Szymczak. Additionally, a peculiar approach of linguists to genus, as a taxonomical unit, has been presented, resulting from lack of understanding of its place and position in the systematics. Finally, proposals were presented of the principles of elaboration of the definitions of family and genus in the descriptive dictionary of Polish.